Implant-supported canine retraction using different reactivation intervals of elastomeric chains: A CBCT-based split-mouth randomized controlled trial - Hend S. ELSAYED; Amr R. EL-BEIALY; Reem ALSHAZLY; Ahmad ALMOHAMMAD; Karim ELAZAB; Rodayna EL-BADAWY; Juan Martin PALOMO; Yehya A. MOSTAFA (Dental Press Editora, 2023)
ABSTRACT Introduction: Orthodontists attempt to maximize treatment efficiency regarding time, tooth position and adverse effects. A new approach, not yet explored, is the activation frequency. Objective: The aim of this split-mouth randomized controlled trial was to evaluate the effect of reactivation intervals on the efficiency of tooth movement. Methods: Thirty eight patients having a Class I malocclusion with bimaxillary dentoalveolar protrusion or severe crowding, Class II with mandibular deficiency or Class III, requiring first premolar extraction and canine retraction were recruited. Elastomeric chains producing 150g were replaced every two, four, six or eight weeks. There were 36, 37, 36, and 36 quadrants randomly allocated to these groups, respectively. The canine retraction rate was the primary outcome. Canine tipping, rotation, and root resorption and pain were the secondary outcomes. Only the outcome assessors were blinded to group assignment. Results: The average total movement for the 6 months was 5.14, 5.31, 2.79 and 3.85 mm for the two-week, four-week, six-week and eight-week reactivation intervals, respectively. Root resorption was significantly higher in the two-week and four-week groups. No adverse events were observed. Conclusion: The canine retraction rate, tipping, rotation and pain were similar in 2, 4, 6 and 8-week activation intervals groups. Longer reactivation intervals show less root resorption. The trial protocol was not pre-registered. The study was self-funded.